PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (FILM DOKUMENTER) - Musdaifa Mansyur; Frida Chairunisa; Nuraeni Sayuti (Politeknik STIA LAN Makassar, 2021)
The Land and Rural and Urban Buildings Tax has been fully managed by local governments including central Mamuju regency. The potential for high acceptance in this sector is expected to be absorbed to the maximum to be utilized in order to improve infrastructure development and community welfare. But the promising potential has not been able to be collected by the government, resulting in year-on-year receivables. The method used in this study is qualitative by conducting eawancara, observation, study documents to obtain information related to the tax of the earth and rural and urban buildings that are poured into the form of documentaries. There is nine informants in this study. Data analysis is done by sorting the results of photos or videos obtained then arranged based on a storyboard or storyline that has been created before. The results show that the process of taxing rural and urban land and buildings still has a number of obstacles that make it difficult for the government to reach its revenue target every year. These include discrepancies in subject data and data objects, a lack of tax awareness, and the difficulty of charging officers to meet the owner of a tax object. Therefore, the government needs to improve the database in a planned manner and make various innovations so that public awareness in fulfilling its obligations can be realized.